Hadith #294 - Sunan al-Nasa'i - Ady bin Dinar al-Madni عدي بن دينار المدني مولى أم قيس; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Umm Qays bint Mihsan al-Asadi; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
“Scratch it, then rub it with water, then sprinkle water over it, and pray in it.”
Grade:

Hadith #395 - Sunan al-Nasa'i - Ady bin Dinar al-Madni عدي بن دينار المدني مولى أم قيس; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Umm Qays bint Mihsan al-Asadi; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
“Scratch it, then rub it with water, then sprinkle water over it, and pray in it.”
Grade:

Hadith #671 - Sunan Ibn Majah - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Ady bin Dinar al-Madni عدي بن دينار المدني مولى أم قيس; Muhammad bin Bashar Bindar محمد بن بشار بندار; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Thabit bin Hurmuz ثابت بن هرمز الكوفي أبو المقدام; Umm Qays bint Mihsan al-Asadi; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Ibn Majah)
“On rainy nights or on cold windy nights, the Messenger of Allah (ﷺ) would summon his announcer to call out: ‘Perform your prayer at your camps.’”
Grade: